Hospital Culture and Healthcare Workers' Provision of Patient-Centered Care: A Moderated Mediation Analysis - Huang, Xianhong; Gao, Yuan; Chen, Hanlin; Zhang, Hao; Zhang, Xiaoting (Frontiers in Public Health, 2022)
Background Patient-centered care (PCC) is globally recognized as a high-quality and high-value healthcare service. It emphasizes the broad participation of patients and families in health-related decision-making and the provision of healthcare services that cater to patients' needs, preferences, and values. However, the mechanisms driving healthcare workers' provision of PCC are yet to be fully uncovered. Methods Using stratified random sampling, we recruited 1,612 healthcare workers from different levels of public hospitals in Hangzhou. We conducted survey interviews using questionnaires based on psychometrically sound scales. Structural equation modeling was used to analyze the effects of hospital culture, self-efficacy, and achievement motivation on the perceived provision of PCC by healthcare workers and to explore the mechanisms underlying their relationships. Results Self-efficacy had a positive mediating effect in the relationship between hospital culture and healthcare workers' perceived provision of PCC (β = 0.424, p < 0.001). Furthermore, the pursuit of success positively moderated the mediating role of self-efficacy (β = 0.128, p < 0.001), whereas, the avoidance of failure negatively moderated the mediating role of self-efficacy (β = -0.017, p < 0.001). Conclusion The findings suggest that hospitals should foster patient-centered and innovative cultures and develop strategies focusing on both internal motivation (self-efficacy and achievement motivation) and external environments (hospital culture) to help and encourage healthcare workers to implement PCC. For example, hospitals could further communication skills training, enhance leadership, build team spirit, and promote collaboration among healthcare workers.